External Validation of COOL-AF Scores in the Asian Pacific Heart Rhythm Society Atrial Fibrillation Registry - Bucci, Tommaso; Shantsila, Alena; Romiti, Giulio Francesco; Teo, Wee-Siong; Chao, Tze-Fan; Shimizu, Wataru; Boriani, Giuseppe; Tse, Hung-Fat; Krittayaphong, Rungroj; Lip, Gregory Y.H. (JACC. Asia, 2024)
The COOL-AF (Cohort of Antithrombotic Use and Optimal International Normalized Ratio Levels in Patients with Atrial Fibrillation) risk scores for death, bleeding, and thromboembolic events (TEs) were derived from the COOL-AF cohort from Thailand and require external validation. The authors sought to externally validate the COOL-AF scores in the APHRS (Asia-Pacific Heart Rhythm Society) registry and to compare their performance in the ESC-EHRA (European Society of Cardiology-European Heart Rhythm Association) EORP-AF (EURObservational Research Programme in Atrial Fibrillation) General Long-Term Registry. We studied 3,628 APHRS and 8,825 EORP-AF patients. Receiver operating characteristic (ROC) curves and Cox regression analyses were used to test the predictive value of COOL-AF scores and to compared them with the CHA2DS2-VASc and HAS-BLED scores. Patients in the EORP-AF were older, had a higher prevalence of male sex, and were at higher thromboembolic and hemorrhagic risk than APHRS patients. After 1 year of follow-up in APHRS and EORP-AF, the following events were recorded: 87 (2.4%) and 435 (4.9%) death for any causes, 37 (1.0%) and 111 (1.3%) major bleeding, and 25 (0.7%) and 109 (1.2%) TEs, respectively. In APHRS, the COOL-AF scores showed moderate-to-good predictive value for all-cause mortality (area under the curve [AUC]: 0.77; 95% CI: 0.71-0.83), major bleeding (AUC: 0.68; 95% CI: 0.60-0.76), and TEs (AUC: 0.61; 95% CI: 0.51-0.71), and were similar to the CHA2DS2-VASc and HAS-BLED scores. In EORP-AF, the predictive value of COOL-AF for all-cause mortality (AUC: 0.68; 95% CI: 0.65-0.70) and major bleeding (AUC: 0.61; 95% CI: 0.60-0.62) was modest and lower than in APHRS. In EORP-AF, the COOL-AF score for TE was inferior to the CHA2DS2-VASc score. The COOL-AF risk scores may be an easy tool to identify Asian patients with AF at risk for death and major bleeding and performs better in Asian than in European patients with AF. (Clinical Survey on the Stroke Prevention in Atrial Fibrillation in Asia [AF-Registry]; NCT04807049) [Display omitted]